PENGARUH KUALITAS PELAYANAN FREIGHT FORWARDING TERHADAP KEPUASAN PELANGGAN DI PT ARINDO JAYA MANDIRI SEMARANG - Devi Kumalasari; Rif’ah Dwi Astuti; Jozef Bambang Tri Joga (Politeknik Negeri Semarang, 2015)
This study aims to identify and explain the Impact of Customer’s Satisfaction Toward Service Quality at PT Arindo Jaya Mandiri Semarang with the population of 32 companies. Data used in this study is primary and the technique to collect data through questionnaire (questionnaire) with numeric scale measurement. To determine the impact of service quality on Customer’s Satisfaction can be partially seen from (T) test calculations and can be simultaneous seen from (F) test calculations. While determination (??) can be used to determine the direct effect of the variable of service upon customer’s satisfaction. After the data were analyzed by SPSS 17 the equation of Y = -3,149 + 0,200 X1 + 0,393 X2 + 0,261 X3 + 0,269 X4 + 0,215 X5 was founded. Further more the coefficient of determination (??) of 0.770 which means that the impact of service quality on customer’s satisfaction was 77% and the restis were determined by factors other than those being used in result of the study. Based on the data processing is done can be viewed and obtained significant value 0.000<0.05 of significance level. Based on the results of research conducted by the 32 respondents, it can be seen that the respondents expressed freight forwarding services is already well. It can be concluded that the hypothesis is accepted, meaning that there is effect of service quality on customers’ satisfaction.